Ameliorative Effects of Dietary Ellagic Acid Against Severe Malaria Pathogenesis by Reducing Cytokine Storms and Oxidative Stress - Mohanty, Shilpa; Gupta, Amit Chand; Maurya, Anil Kumar; Shanker, Karuna; Pal, Anirban; Bawankule, Dnyaneshwar Umrao (Frontiers in Pharmacology, 2021)
Ellagic acid (EA), a fruits and vegetables-derived flavonoid has been reported for multiple pharmacological activities which encouraged us to examine its useful effect in severe malaria pathogenesis especially malaria-induced cytokine storms and oxidative stress linked to damage in major organs. Malaria was induced by Plasmodium berghei infected RBC’s given intra-peritoneally into the mice. EA was given orally (5, 10 and 20 mg/kg) following Peter’s 4 day suppression test. EA exhibited suppression of parasitaemia, production of inflammatory cytokine storms and oxidative stress markers level quantified from vital organs significantly and increase in haemoglobin, blood glucose and mean survival time compared to vehicle-treated infected group. EA administration also restored blood-brain-barrier integrity evidenced through Evans blue staining. Furthermore, we demonstrated protecting effect of EA in LPS-induced inflammatory cytokines storms and oxidative stress in glial cells. The present study conclude that ellagic acid is able to alleviate severe malaria pathogenesis by reducing cytokine storms and oxidative stress-induced by malaria parasites. It also attributed promising anti-malarial activity and affords to improve the blood glucose, haemoglobin level in treated mice. These research findings suggested the suitability of ellagic acid as a useful bioflavonoid for further study for the management of severe malaria pathogenesis